Safety of switching from vitamin K antagonists to dabigatran or rivaroxaban in daily care – results from the Dresden NOAC registry. (October 2014) - Beyer‐Westendorf, Jan; Gelbricht, Vera; Förster, Kati; Ebertz, Franziska; Röllig, Denise; Schreier, Thomas; Tittl, Luise; Thieme, Christoph; Hänsel, Ulrike; Köhler, Christina; Werth, Sebastian; Kuhlisch, Eberhard; et al.
<x xml:space="preserve">Abstract</x> Aim Vitamin‐K antagonists (VKA) and non‐vitamin‐K dependent oral anticoagulants (NOAC) have been approved for anticoagulation in venous thromboembolism (VTE) and atrial fibrillation and patients previously treated with VKA are switched to NOAC therapy. Safety data for this switching are urgently needed. Methods Using data from a large regional prospective registry of daily care NOAC patients, we evaluated the safety of switching anticoagulation from VKA to dabigatran or rivaroxaban. Switching procedures and cardiovascular and bleeding events occurring within 30 days after switching were centrally adjudicated. Results Between 1 October 2011 and 18 June 2013, 2231 patients were enrolled. Of these, 716 patients were switched from VKA to NOAC. Only 410 of the 546 evaluable patients (75.1%) had a recorded INR measurement within the 10 days preceding or following the end of VKA treatment (mean INR 2.4). As of day 30, major bleeding complications were rare (0.3%; 95% CI 0.0, 1.0) with an overall bleeding rate of 12.2% (95% CI 9.8, 14.8). Major cardiovascular events occurred in 0.8% (95% CI 0.3, 1.8). There was no significant difference in outcome event rates between the subgroups of patients with or without INR testing. Conclusion In daily care, only 75% of VKA patients have an INR measurement documented before NOAC are started. On average, NOAC are started within 2 to 5 days after the last intake of VKA. However, at 30 days follow‐up cardiovascular events or major bleedings were rare both in patients with and without INR testing. However, switching procedures need to be further evaluated in larger cohorts of patients.